Assessing the Patterns of Gynecological Cancers Treated at Jordan University Hospital: A Retrospective Study - Kamil M. Fram; Asma S. Albasha; Farah K. Fram; Rand K. Fram; Sewar Bishara; Mosa K. Fram; Fadi R. Odetallah; Lara I. Abdillat; Gadeer Alsbateen (Achievements and Challenges of Medicine and Medical Science Vol. 1, 2024)
Background: Jordan is a developing country occupying the heart area of the Middle East with a total area of 89,342 km2, the population is 11,552,876 in 2024, and the population world rank is 84. Objectives: The goal of this study was to assess the patterns of gynecological cancers treated at the Department of Gynecology and Obstetrics at Jordan University Hospital (JUH) by reviewing patient records retrospectively. Materials and Methods: The study included all patients diagnosed with primary gynecologic cancers who underwent surgical treatment at JUH between June 2013 and June 2017. The imaging tools used were CT scan, MRI, PET, or a combination according to the case. Key data such as cancer type, age distribution, cancer incidence, and disease stage at diagnosis were reviewed and analyzed. Results: A total of 115 cases of gynecological cancers were recorded during the study period. The average age of the patients was 58.56 years. Uterine cancer was the most commonly diagnosed, accounting for 50 cases (43.38%), followed by 38 cases of ovarian cancer. There were also 18 cases of cervical cancer, with vulvar/ vaginal cancer in 9 cases combined. The average age for patients with endometrial cancer was 57.17 years, ovarian cancer 56.11 years, and cervical cancer 62.22 years. Most cases of endometrial and cervical cancers were diagnosed at Stage I, whereas ovarian cancer was more often found at an advanced stage. Conclusion: Endometrial and ovarian cancers are the most common gynecological malignancies in Jordan. Cancer remains a significant public health challenge and continues to pose a serious public health challenge in the country, underscoring the urgent need for strategic interventions. Accurately estimating and forecasting cancer trends is vital for informed healthcare planning and resource distribution. The study emphasized that a powerful reminder to keep in mind is that no one, regardless of age, marital status, or financial standing, is immune to cancer.